2018
DOI: 10.1093/jncics/pky005
|View full text |Cite
|
Sign up to set email alerts
|

Major Impact of Sampling Methodology on Gene Expression in Estrogen Receptor–Positive Breast Cancer

Abstract: To investigate the impact of sampling methodology on gene expression data from primary estrogen receptor–positive (ER+) breast cancer biopsies, global gene expression was measured in core-cut biopsies at baseline and surgery from patients randomly assigned to receive either two weeks of presurgical aromatase inhibitor (AI; n = 157) or no presurgical treatment (n = 56). Those genes most markedly altered in the AI group (eg, FOS, DUSP1, RGS1, FOSB) were similarly altered in the no treatment group; some widely in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 6 publications
0
19
0
Order By: Relevance
“…It appears that the upregulation of these genes may be related to longer time to fixation for the surgical samples rather than study-related as four of these genes were also up regulated in our studies of changes in gene expression in the absence of drug-treatment. 15,16 These five genes were excluded from further analysis, as any changes in their expression between windows could not be ascribed with confidence to menstrual cycle effects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It appears that the upregulation of these genes may be related to longer time to fixation for the surgical samples rather than study-related as four of these genes were also up regulated in our studies of changes in gene expression in the absence of drug-treatment. 15,16 These five genes were excluded from further analysis, as any changes in their expression between windows could not be ascribed with confidence to menstrual cycle effects.…”
Section: Resultsmentioning
confidence: 99%
“…Tumour samples taken in the same window of the menstrual cycle provided a control group and indicated that the expression of five of our selected genes increased between diagnosis and surgery irrespective of cycle window. The upregulation of these genes does not appear to be study-related as four of these genes were also upregulated in studies of changes in gene expression in the absence of drug-treatment 15,16 where the upregulation was ascribed to differences in the time taken to fixation for the samples at the two time points. These five genes were thus excluded from further analysis, as any changes in their expression between different windows would not be attributable to menstrual cycle effects.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, and importantly, previous reports have not included controls that can identify artefacts that result from the experimental design of pre-surgical studies; we have recently reported that the changes in gene expression of the greatest magnitude in AI-treated patients in a short-term presurgical study are entirely artefactual. This makes the inclusion of a control set of tumours critical for eliminating these artefacts [13]. In the following analyses, we have utilised a study design that avoids these limitations by accessing samples from the PeriOperative Endocrine Therapy-Individualising Care (POETIC, CRUK/07/015) trial [14].…”
Section: Introductionmentioning
confidence: 99%
“…Given the central role gene expression analyses play in the investigation and management of breast cancer, the report by Gao et al (17), describing artifactual gene expression changes in serially sampled specimens collected as part of a randomized controlled trial, are particularly relevant to the design and interpretation of gene expression biomarker studies. In their accompanying article, the authors build on previous reports describing alterations in gene expression related to delays in tissue processing following sampling, including substantial changes in early response genes between diagnostic core biopsies and surgical specimens (18–20).…”
mentioning
confidence: 99%
“…This would result in substantial differences in ischemic time that could produce cellular responses and affect sample integrity. Gao et al showed that many of the genes whose expression is most altered between baseline and surgery in the AI-treated group are also those affected in the control arm (Figure 1) (17). This is a striking finding as it indicates that the genes that could have been attributed to AI treatment were actually due to a confounding factor.…”
mentioning
confidence: 99%